The Toys "R" Us LBO - Stowell, David P.; Raino, Matthew (London : SAGE Publications Ltd, 2017)
The case simulates the experience of a private equity investor evaluating a potential investment, requiring the student to: (1) determine the risks and merits of an investment in Toys "R" Us, (2) evaluate the spectrum of returns using multiple operating model scenarios, and (3) identify strategic actions that might be undertaken to improve the risk/return profile of the investment. The case also discusses trends and participants in the private equity industry.
Originally published: Stowell, D. P., & Raino, M. (2007). The Toys "R" Us LBO. 5-107-002. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Toys "R" Us (Firm); Private equity -- Case studies; Investments -- Case studies; Risk assessment -- Case studies; Financial services industry -- Case studies